2014
DOI: 10.1007/s10865-014-9565-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of weight regain in the weight loss maintenance trial

Abstract: This study's purpose was to identify psychosocial predictors of weight loss maintenance in a multi-site clinical trial, following a group-based weight loss program. Participants (N = 1025) were predominately women (63 %) and 38 % were Black (mean age = 55.6 years; SD = 8.7). At 12 months, higher SF-36 mental health composite scores were associated with less weight regain (p < .01). For Black participants, an interaction existed between race and friends' encouragement for exercise, where higher exercise encoura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 54 publications
(73 reference statements)
7
41
0
Order By: Relevance
“…In contrast, the DE group was able to maintain lifestyle habits learned in their supervised programme. A meta‐analysis of weight‐loss programmes found that self‐monitored programmes had adherence rate of ~40% compared to ~70% in supervised interventions, while individuals who received guided support were 37% more likely to maintain weight loss than those with self‐directed strategies . The American College of Sports Medicine recommends at least 200 minutes per week of moderate‐intensity exercise (~1200 MET‐minutes/week, comparable to our DE group and significantly more than our LI group) to prevent weight regain .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, the DE group was able to maintain lifestyle habits learned in their supervised programme. A meta‐analysis of weight‐loss programmes found that self‐monitored programmes had adherence rate of ~40% compared to ~70% in supervised interventions, while individuals who received guided support were 37% more likely to maintain weight loss than those with self‐directed strategies . The American College of Sports Medicine recommends at least 200 minutes per week of moderate‐intensity exercise (~1200 MET‐minutes/week, comparable to our DE group and significantly more than our LI group) to prevent weight regain .…”
Section: Discussionmentioning
confidence: 75%
“…37 Weight regain in the LI group of ~1.8% was comparable to that seen after liraglutide was discontinued in the SCALE Maintenance study 38 while individuals who received guided support were 37% more likely to maintain weight loss than those with self-directed strategies. 40 The American College of Sports Medicine recommends at least 200 minutes per week of moderate-intensity exercise (~1200 MET-minutes/week, comparable to our DE group and significantly more than our LI group) to prevent weight regain. 18 Physical activity level protects against development of NAFLD independent of insulin resistance and visceral adiposity, 41 were found to be more responsive biomarkers compared to histology 42 and cCK-18 changes have been correlated with histological progression.…”
Section: Assessment For Eligibilitymentioning
confidence: 76%
“…Within 1 year, 50% of people who engage in a weight‐loss intervention will experience weight regain (Palascha, van Kleef, & van Trijp, ). Current research indicates weight maintenance and regain are complex, and affected by the interaction of a variety of physiologic, genetic, and psychosocial factors (Brantley et al., ; Palascha et al., ; Papandonatos et al., ; Rogge & Gautam, ). Studies to determine more effective strategies to promote and maintain weight loss are ongoing; emerging results may offer insight.…”
Section: Need For Improved Training Resources and Reimbursementmentioning
confidence: 99%
“…In the current study, no significant correlations were observed between baseline PSS and the weight loss effect, but the small sample size may have weakened the power to detect a significant association should it have been present. In a US weight loss trial, the perceived stress was predictive of weight regain during the maintenance period in previous weight loss interventions [38] [39]. Future interventions with larger sample size are warranted to provide more evidence on how baseline stress levels might predict weight loss levels, and take into consideration emotional management in obesity prevention.…”
Section: Associations Of Stress Levels With Baseline Adiposity and Chmentioning
confidence: 96%